Reading Rick Riordan'S Sea Of Monsters Using Propp'S Theory Of Narratology - Khaksari, Mahta (2019)
Due to the significance of the contemporary young adult literature (YAL) in conveying values and literary information to young readers, and because such texts appeal to young adults (YA) more than the classics, the present research aims to investigate the structure of modem mythology texts systematically to see whether they match the classics in terms of complexity of structure and conveyed values or not. To this end, the structure of YA novel Percy Jackson and (he Sea of Monsters (SaM) by Riordan (2013) was analysed based on the theory of narratology of Propp (1968/2009) presented in Morphology ofthe Folktale. The functions of the characters and their corresponding sequence and move schemes were identified and the Proppian move schemes were combined and extended into a new move scheme representing a heroic type of novel.